Analisis Metode Penemuan Hukum Dalam Yurisprudensi Wanprestasi Bukan Tindak Pidana Penipuan (Legtimacy: Journal of Law and Islamic Law, 2025)
The crime of fraud and breach of contract are two different things. Breach of contract is a civil law matter that occurs due to negligence after an agreement is made and the settlement of the case is carried out civilly. Meanwhile, fraud is included in the realm of criminal law with the main element of deception from the beginning or before the agreement is made and must fulfill two main things, namely mens rea/guilty mind and actus reus/guilty act. However, in practice, sometimes people are reported to the police for breach of contract or breach of promise and end up in prison. This study aims to analyze the legal discovery/legal interpretation techniques used by Judges in creating Jurisprudence Number 4/Yur/Pid/2018. The research method used is normative juridical with a statutory approach, a case approach, and a conceptual approach. The research results show that judges used two methods in creating Jurisprudence Number 4/Yur/Pid/2018. This jurisprudence not only fills the gap in norms but also to prevent the misuse of criminal fraud provisions and ensure that contractual failures are resolved through civil proceedings.